Awake Craniotomy Under 3-Tesla Intraoperative Magnetic Resonance Imaging: A Retrospective Descriptive Report and Canadian Institutional Experience. Issue 1 (29th January 2022) - Chowdhury, Tumul; Zeiler, Frederick A.; Singh, Narinder; Gray, Kristen D.R.; Qadri, Ali; Beiko, Jason; Cappellani, Ronald B.; West, Michael
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The role of high-field 3-Tesla intraoperative magnetic resonance imaging (I-MRI) during awake craniotomy (AC) has not been extensively studied. We report the feasibility and safety of AC during 3-Tesla I-MRI. Methods: This retrospective descriptive report compared 3 groups: AC with minimal sedation and I-MRI; I-MRI-guided craniotomy under general anesthesia (GA), and; AC without I-MRI. Perioperative factors, surgical, anesthetic and radiologic complications, and postoperative morbidity and mortality were recorded. Results: Overall, 85 patients are included in this report. Five of 23 patients (22%) who underwent AC with I-MRI had anesthetic complications (nausea/vomiting and conversion to GA) compared with 3 of 40 (8%) who underwent I-MRI-guided craniotomy under GA (nausea/vomiting during extubation, and arrhythmia). Intraoperative surgical complications (seizures and speech deficits) occurred in 5 patients (22%) who underwent AC and I-MRI, excessive intraoperative bleeding occurred in 2 patients (5%) who had I-MRI-guided craniotomy under GA, and 4 of 22 (18%) patients who underwent AC without I-MRI experienced neurological complications (seizures, motor deficits, and transient loss of consciousness). Eight patients (20%) who had I-MRI with GA had postoperative complications, largely neurological. The duration of surgery and anesthesia were shortest in the group of patients receiving AC without I-MRI. Seventy-three percent of the patients in this group had residual tumor postoperatively compared with 44% and 38% in those having I-MRI with AC or GA, respectively. Patients who underwent I-MRI-guided craniotomy with GA had the highest morbidity (8%) at hospital discharge. Conclusions: Our institutional experience suggests that AC under 3-Tesla I-MRI could be an option for glioma resection, although firm conclusions cannot be drawn given the limited and heterogenous nature of our data. Future multicenter trials comparing anesthetic and imaging modalities for glioma resection are recommended.